Experimental bovine rotavirus-A (RV-A)infection causes intestinal and extra-intestinal pathology in suckling mice. (August 2018) - Kashyap, Gayatri; Singh, R.; Malik, Y.S.; Agrawal, R.K.; Singh, K.P.; Kumar, P.; Sahoo, M.; Gupta, D.; Singh, Rahul
Abstract: We describe here the intestinal and extra-intestinal spread of the species A rotavirus (RV-A) and associated lesions thereof in Swiss albino suckling mice pups, inoculated with a bovine-origin RV-A strain. In total, 35 suckling pups were used, wherein 20 pups received cell culture isolated RV-A @ 160 μL (TCID50 /ml, 5 × 10 6.5 ) per pup [oral 80 μL and intra peritoneal (IP) 80 μL] and served as an infected group, while 15 pups were kept in the control group and inoculated the same volume of phosphate buffered saline (PBS) of neutral pH orally and IP. Four pups from the infected group and 3 from control group were sacrificed at 3, 5, 7, 9 and 12 day post infection (DPI). Of note, infected pups exhibited signs of dullness and restlessness till 5DPI, but none showed diarrhea at any point of time. No appreciable gross lesions were evident in any of the organs, except for mild congestion of the small intestine and yellowish catarrhal smearing over the luminal surface. However, light microscopic lesions in hematoxylin and eosin (H&E) stained sections of jejunum and ileum revealed vacuolation and pyknosis of nuclei of the mature enterocytes, their lysis and detachment, constriction and detachment of villi, mild mononuclear cells (MNCs) infiltration in the lamina propria and mildcell depletion of Peyer's patches and mesenteric lymph nodes (MLN). The extra-intestinal lesions of the cellular degeneration and mild MNCs infiltration were identified in the liver and kidneys from 3 to 7 DPI, but no lesion was seen in the brain. Interstitial thickening with MNCs of lung parenchyma was visible from 3 to 7 DPI. The lesions in the intestine, lymphoid tissues and lungs resolved after 7 DPI. The presence of viral nucleic acid was seen in the intestinal contents from 3 to 5 DPI by using a RV-A specific reverse-transcription polymerase chain reaction (RT-PCR), while in the MLNs and the lungs it could be detected till 5 DPI by both the RT-PCR and direct fluorescent antigen test (dFAT). However, liver, spleen and brain were tested negative for the presence of RV-A by any of these tests. Nonetheless, the persistence of the RV-A was seen in the MLNs even after the absence of virus from the small intestines. Findings here conclusively indicates that heterologous host origin RV-A has an affinity not only to the intestine but also to extra-intestinal tissues like MLNs and lung tissues. Highlights: Heterologous bovine-origin RV-A strain experimentally establishes virus specific enteric infection. Extra-intestinal pathology also evident in lungs, mesenteric lymph nodes after infection at 3 and 5 DPI. Infection established in suckling mice by using both oral and IP routes, simultaneously. Suckling mice is a laboratory model to study the bovine or other heterologous RV-A strains pathogenesis.